Peningkatan Hasil Belajar IPA Melalui Model Pembelajaran Think-Talk-Write Bervariasi pada Siswa Kelas VIII.H SMP Negeri 2 Banyudono Semester 1 Tahun Pembelajaran 2013/2014 - DWI GIYARNI (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2016)
Application of learning models talk think write varied in an effort to improve student achievement and to increase the interest, motivation, liveliness, creativity, and cooperation of the students in the class IPA maple VIII.H half SMP Negeri 2 Banyudono of the school year 2013/2014. Hypothesis test results obtained from VIII.H grade students of SMP Negeri 2 Banyudono maple IPA 2012/2013 school year on Standards of Competence Understanding the Different Systems In Human Life that: 1) the results of student achievement has increased from the initial conditions to final conditions of the first cycle and continued to the second cycle there is increased as follows: for the highest value of 80 increased to 90 in the first cycle, and increased again to 95 in the second cycle, to the lowest value of 50 rose to 75 in the first cycle, and rose again to 76 in the second cycle, for the average value of 66.25 on Prasiklus rose to 78.61 in the first cycle, and rose again to 85.08 in the second cycle, students complete of 15 (41.67%) rose to 36 students (100%) cycles I, and the second cycle, for students not yet complete of 21 students dropped to 0 students in the first cycle and the second cycle. 2) The process of learning: increased from the initial conditions to final conditions of the first cycle and proceed to the second cycle: Interest 1.95 (or less) to 3.23 (good) and increased again to 3.47 (good). Motivation 2.03 (enough) to 3.13 (good) and increased again to 3.46 (good). Liveliness 1,99 (less) to 3.18 (good) and increased again to 33.45 (good). Creativity 1.83 (or less) to 3.13 (good) and increased again to 3.35 (good) Cooperation 2.04 (enough) to 3.22 (good) and increased again to 3.53 (good). Keywords: IPA, Model think-talk-write, Interest, Motivation, Liveliness and Creativity, Cooperation, Results Achievemen